Pengaruh Alokasi Dana Desa, Kebijakan Desa, dan Badan Usaha Milik Desa Terhadap Kesejahteraan Masyarakat Desa Karyalaksana Kecamatan Ibun Kabupaten Bandung - Saputra, Syahdan Arip; Manjaleni, Rola (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study examines the influence of village fund allocations, village policies, and Village-Owned Enterprises (BUMDes) on community welfare in Karyalaksana Village, Ibun Subdistrict. This study used quantitative methods with a sample of 96 people and conducted multiple linear regression to determine the relationship between the independent variables and community welfare, which is the dependent variable. The results showed that collectively, the three factors had a significant effect on community welfare, with village policy being the most influential factor. The results of this study reinforce that effective village governance is essential for improving community welfare. In addition, transparency in the management of village funds and community involvement in the formulation of village policies are important components for achieving optimal development outcomes. The implication is that village governments need to improve the effectiveness of BUMDes policies and management to provide wider economic impact. This study also provides insights for academics and practitioners in developing good governance-based development strategies.